TEORI PERSEPSI MULLÂ SHADRÂ BESERTA IMPLIKASI EPISTEMOLOGI DAN METODOLOGISNYA UNTUK PSIKOLOGI - Husein Heriyanto (Jurnal Studia Insania, 2015)
Human action is seen as behavior of organisms that are subject to the law of effect (the law of effect) through the process of reinforcement and punishment, stimulus-response mechanism, learning by trial, and the laws of Biochemistry and physiological. Mullâ Shadrâ has brought us to a new consciousness that we are over this as if asleep because it doesn’t realize that all our actions including sensory perception is our soul’s activity directly. Epistemolois and methodological implications of the theory of perception Shadrâ this potentially to do a revolution in psychology, that relives live, i.e. as a single agent – holistic in all the actions of our perception and cognition